If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + 3 = -8(y + 6) Reorder the terms: 3 + 9y = -8(y + 6) Reorder the terms: 3 + 9y = -8(6 + y) 3 + 9y = (6 * -8 + y * -8) 3 + 9y = (-48 + -8y) Solving 3 + 9y = -48 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 3 + 9y + 8y = -48 + -8y + 8y Combine like terms: 9y + 8y = 17y 3 + 17y = -48 + -8y + 8y Combine like terms: -8y + 8y = 0 3 + 17y = -48 + 0 3 + 17y = -48 Add '-3' to each side of the equation. 3 + -3 + 17y = -48 + -3 Combine like terms: 3 + -3 = 0 0 + 17y = -48 + -3 17y = -48 + -3 Combine like terms: -48 + -3 = -51 17y = -51 Divide each side by '17'. y = -3 Simplifying y = -3
| 7(9+7k)=84 | | 5x^3-y-1=0 | | -39+3x=15+5x | | -16+x/4= | | 7(7-x)=1.5(5-x) | | 4/9x7/3 | | 2/3x=216 | | 4/9x13/4 | | 5x-40=2y | | 1/2x-41=181 | | -x-91=96+10x | | 5-x/6=-1 | | 400000/12=53000000/x | | 100m^2=26m | | 28x^2+20x= | | 5z=1.7+5.8 | | 5x-96=-6x+69 | | 5x+40=12x | | 7/12=2/x | | +1x=-8 | | 58-3/4x11 | | 2x+3x+10x=180 | | x=-4+1 | | 1.25x=0.75x+.50 | | y=(x-2)(x+7) | | (7x-4)(8x+4)=0 | | 4/5×m=1 | | 3x+11=x+21 | | 7x-10x-20=11 | | X-1/2=2x-3/5 | | 7x+9=100-x-3 | | (9pq^6-11p^4q)-(-5pq^6+p^4q^4)= |